Strategies for improving early detection of glaucoma: the combined structure–function index - Tatham, Andrew J (Dove Medical Press, 2014)
The early detection of glaucoma is important in order to enable appropriate monitoring and treatment, and to minimize the risk of irreversible visual field loss. Although advances in ocular imaging offer the potential for earlier diagnosis, the best method is likely to involve a combination of information from structural and functional tests. Recent studies have shown it is possible to estimate the number of retinal ganglion cells from optical coherence tomography and standard automated perimetry, and to then pool the results to produce a combined structure–function index (CSFI). The CSFI represents the estimated percentage of retinal ganglion cells lost compared to an age-matched healthy eye. Previous studies have suggested that the CSFI is better able to detect glaucoma than isolated measures of structure and function, and that it performs well even in preperimetric glaucoma. The purpose of this review is to describe new strategies, such as the CSFI, that have the potential to improve the early detection of glaucoma. We also describe how our ability to detect early glaucoma may be further enhanced by incorporating demographic risk factors, clinical examination findings, and imaging and functional test results into intuitive models that provide estimates of disease probability.